Pengaruh Model Pengukuran Formatif Terhadap Need For Closure Konsumen - Sari, Mustika (Economic Management Business Research Journal, 2025)
Need for closure is a new construct in consumer behavior and marketing management research. This construct is considerably robust to measure consumer’s epistemic motivation. Epistemic motivation is a desire based action to obtain relevant knowledge to make judgment or buying decision. Previous study measures need for closure construct with reflective measurement model specification. Conceptual analysis shows that need for closure construct is a formative model due to the equality of its dimensions. This study shows strong evidence that formative measurement model specification is more robust than reflective model to test the model of influence of need for closure of online consumer and flow level in the internet environment